2014 IEEE Electrical Insulation Conference (EIC) 2014
DOI: 10.1109/eic.2014.6869413
|View full text |Cite
|
Sign up to set email alerts
|

Slot corona protection systems for medium voltage rotor windings subjected to PWM voltage in doubly fed induction generators

Abstract: Doubly fed induction generators using static frequency converters provide the possibility to have adjustable speed pump storage units where the active power can be controlled quickly for both generation (energy discharge) and pumping (energy storage) operation. However, high magnitude voltage spikes with high repetition rate and fast rise times (associated with PWM voltage of the converter) applied to the rotor winding, have adverse effects on the rotor insulation system. In this study using IEC 60034-18-42 te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The tangential component of the electric field in the CAT is well below the tangential electric fieldint heSGT (Figure 17(a)), but the heat generated in this coating is considerably higher (Figure 17(b)). Experimental work on form-wound coils stressed by fast pulses has shown that this condition can damage the CAT, allowing surface PD to appear right at the slot exit [51,52]. The next section introduces the use of FEM modeling to investigate possible solutionstothisproblem.…”
Section: Simulation and Modelling Of Electrical Insulation Weaknessesmentioning
confidence: 99%
“…The tangential component of the electric field in the CAT is well below the tangential electric fieldint heSGT (Figure 17(a)), but the heat generated in this coating is considerably higher (Figure 17(b)). Experimental work on form-wound coils stressed by fast pulses has shown that this condition can damage the CAT, allowing surface PD to appear right at the slot exit [51,52]. The next section introduces the use of FEM modeling to investigate possible solutionstothisproblem.…”
Section: Simulation and Modelling Of Electrical Insulation Weaknessesmentioning
confidence: 99%